Reporting Racist Hate Crime Victimization to the Police in the United States and the United Kingdom: A Cross-National Comparison - Myers, Wesley (The British journal of criminology, 2020)
Hate is a global phenomenon as evidenced by recent increases in hate crimes in both the United States and the United Kingdom; unfortunately, these crimes are also substantially underreported in both nations. Following this, this research presents an examination of racially motivated hate crimes and victim reporting to the police in both nations using data from the National Crime Victimization Survey and the Crime Survey of England and Wales from 2003 to 2015. Results indicate that, overall, victim reporting has been increasing in the United Kingdom and decreasing in the United States. Disaggregating by victim and offender race, however, reveals divergent trends such that anti-black hate crime victim reporting is increasing in the United States and decreasing in the United Kingdom. Policy and research implications are discussed.